THE IMPORTANCE OF THE SPIRITUAL HERITAGE OF THE JADIDISTS IN THE UPBRINGING OF A MATURE GENERATION DURING THE PERIOD OF INDEPENDENCE OF UZBEKISTAN (Web of Humanities: Journal of Social Science and Humanitarian Research, 2024)
Building society in Uzbekistan on a fundamentally new basis and its comprehensive development is directly related to the worldview and spirituality of the people. The country's independence, development, people's happiness, faith, the sense of the Motherland, freedom are determined in a certain way by the level of the spiritual environment in the society. The First President of the Republic of Uzbekistan, IAKarimov, in his work "High Spirituality - Invincible Power" emphasized that spirituality is an important condition and guarantee for the sustainable development of society and writes: "The experience of the peoples of the world, the complex development path they have gone through. lessons and conclusions in this regard indicate that wherever the state and society progress, there are sufficient conditions for the people to live peacefully, to live with noble and great goals. an environment of free thinking and on this basis new opportunities for spiritual growth are born.